Neural Dynamic Responses of Monetary and Social Reward Processes in Adolescents - Wang, Di; Liu, Tongran; Shi, Jiannong (Frontiers in Human Neuroscience, 2020)
We investigated the development of monetary and social reward processes in children, adolescents and adults by employing adapted incentive delay tasks with event-related potential (ERP) recordings. The behavioral results showed that both monetary and social rewards could motivate participants' response speed, and they had higher accuracy under monetary reward condition than that under social reward condition. Individuals' behavioral performances increased with age. For the ERP data, the cue-P3, target-P2, target-P3 and feedback-related negativity (FRN) components were investigated to identify reward motivation, emotional arousal, attention allocation and feedback processing. Children and adolescents showed higher motivation (larger cue-P3) to rewards than adults. Adolescents’ emotional responses to reward (target-P2) were more sensitive to social rewards than children and adults and were effectively regulated by different magnitudes of social rewards. Children showed stronger emotional reactivity for monetary rewards than for social rewards. All the age groups had stronger attentional control (larger target-P3) under monetary reward condition than that under social reward condition. The present study shed the light on the neurodevelopment of reward processes from children, adolescents to adults, and varied reward process stages demonstrated different age-related and reward type-related characteristics.